Do Trade Openness, Human Capital, and Good Governance Affect Green Energy Consumption: New Evidence from (G7) - Muqdad Zaki Hammed Banana; Malik Abdul Raheem Mohammed (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Green energies are more adapted to the environment, and their production and production are less polluted. Moreover, since there is no end to this energy category, green energies are taking on an ever-increasing share of the world's energy supply system, even in countries with fossil fuels. The current study aims to examine the factors affecting green energy consumption in Group 7 countries using a table-based data approach (Panel data quantile regression) from 1996-2022. The study examined how financial impacts such as the Good Governance Index (GGI), Human Capital (MYS), Trade Openness (TO), Income (GDP), Inflation (INFL) and Non-Financial Fixed Capital Formation (GFCF) are affected. Thus, assuming the stability of other factors, by an increase of one unit in GGI, MYS, TO, GDP, INFL, and GFCF, green energy consumption (GEC) increases between 0.24 and 0.59%, 2.46 to 7.12%, 0.98 to 1.53%, 0.73 to 1.03%, 0.42 to 0.62% and 1.07 to 1.73%. Given the positive and meaningful impact of the Good Governance Index and Human Capital on green energy consumption, it is proposed to double attention to the quality of laws and regulations, the rule of law, and the design and enforcement of laws in protecting the environment and developing more clean energies. The results can be an outstanding lesson for creating and developing countries.